The strategy of Willen and Phillips and its impact on positive thinking and teaching the skills of the long serve and the backhand stroke in badminton to students (Global Scientific Review, 2024)
The importance of the research lies in using the Willen and Phillips strategy to determine the extent of its impact on positive thinking and teaching the skills of the long serve and the backhand volley to students. As for the problem of the research, the researcher noticed that most students suffer from difficulty in performing the skills of the long serve and the backhand volley and fluctuation in level. Performance and accuracy may be due to the lack of practice and repetition during lecture time and the lack of use of educational strategies that give ample opportunity to practice the learning process. As for the objectives of the research, the most important of them was building a measure of positive thinking, identifying the effect of the Willen and Phillips strategy on positive thinking, and learning the skills of the long serve and the backhand stroke in the shuttlecock. The plane was for the students. The population and sample of the research were third-level students in the College of Physical Education and Sports Sciences at Dhi Qar University